(ZrB2–SiC)/SiC oxidation protective coatings for graphite materials. Issue 5 (June 2015) - Wang, Peng; Han, Wenbo; Zhang, Xinghong; Li, Ning; Zhao, Guangdong; Zhou, Shanbao
Abstract: ZrB2 –SiC coatings were prepared on the SiC coated specimens by pack cementation method at 1900 °C for 2 h. The phase, microstructure, anti-oxidation and thermal shock resistance properties of these coatings were investigated. It was found that ZrB2 –SiC coatings improved anti-oxidation and thermal shock resistance. ZS50 coating endured 15 thermal shock cycles between 1500 °C and room temperature with 20.2% weight loss, which was attributed to the dense glass phase formed after oxidation.